Contrived Resemblance: Delaroche and Napoleon - Lisa Hackmann (Journal for Art Market Studies, 2018)
Several contemporaries highlighted the physical resemblance between Delaroche and Napoleon, of which Delaroche appears to have been acutely conscious. The way the painter’s identification with the French emperor has been understood in academic research bears the clear hallmark of biographically psychologising interpretations. This article proposes an alternative way of interpreting this staged similarity between Delaroche and Napoleon. This interpretation derives firstly from an observation of the drastic change in the artist’s professional circumstances that took place in the late 1830s, and then takes into consideration the specific characteristics of Napoleon’s popularity in the 1820s, which precipitated multiple forms of projection and identification. Largely depoliticised, the immediately recognisable figure of Napoleon cut across national and social boundaries, and had tremendous potential for marketing. During the 1840s and 1850s, the visibility of Delaroche’s pictures extended beyond Europe – not only as a result of the reproductions in circulation, but also by virtue of numerous versions painted by the artist’s own hand. Given this wider context, it may well be assumed that Delaroche’s staged similarity to Napoleon was an experiment in form and a way to establish an image compatible with the demands of the public market and mass audiences. He very adeptly used his paintings to link this image to the cult figure of Napoleon. In a period in which the artist was forging a new career path, he found himself faced with the challenge of responding to an art market of increasing structural and geographic complexity by adopting innovative self-marketing strategies.